Causes and risk factors for death in systemic sclerosis: a study from the EULAR Scleroderma Trials and Research (EUSTAR) database. Issue 10 (15th June 2010) - Tyndall, Anthony J; Bannert, Bettina; Vonk, Madelon; Airò, Paolo; Cozzi, Franco; Carreira, Patricia E; Bancel, Dominique Farge; Allanore, Yannick; Müller-Ladner, Ulf; Distler, Oliver; Iannone, Florenzo; Pellerito, Raffaele; et al.
Abstract : Objectives: To determine the causes and predictors of mortality in systemic sclerosis (SSc). Methods: Patients with SSc (n=5860) fulfilling the American College of Rheumatology criteria and prospectively followed in the EULAR Scleroderma Trials and Research (EUSTAR) cohort were analysed. EUSTAR centres completed a structured questionnaire on cause of death and comorbidities. Kaplan–Meier and Cox proportional hazards models were used to analyse survival in SSc subgroups and to identify predictors of mortality. Results: Questionnaires were obtained on 234 of 284 fatalities. 55% of deaths were attributed directly to SSc and 41% to non-SSc causes; in 4% the cause of death was not assigned. Of the SSc-related deaths, 35% were attributed to pulmonary fibrosis, 26% to pulmonary arterial hypertension (PAH) and 26% to cardiac causes (mainly heart failure and arrhythmias). Among the non-SSc-related causes, infections (33%) and malignancies (31%) were followed by cardiovascular causes (29%). Of the non-SSc-related fatalities, 25% died of causes in which SSc-related complications may have participated (pneumonia, sepsis and gastrointestinal haemorrhage). Independent risk factors for mortality and their HR were: proteinuria (HR 3.34), the presence of PAH based on echocardiography (HR 2.02), pulmonary restriction (forced vital capacity below 80% of normal, HR 1.64), dyspnoea above New York Heart Association class II (HR 1.61), diffusing capacity of the lung (HR 1.20 per 10% decrease), patient age at onset of Raynaud's phenomenon (HR 1.30 per 10 years) and the modified Rodnan skin score (HR 1.20 per 10 score points). Conclusion: Disease-related causes, in particular pulmonary fibrosis, PAH and cardiac causes, accounted for the majority of deaths in SSc.